Model Perkawinan Sirri dan Akibat Hukum Bagi Anak dan Istri - Suprayogi, Rizqi; ‎ ‎ ‎, Fredy Gandhi Midia (Syakhsiyah Jurnal Hukum Keluarga Islam, 2022)
Marriage holds significant value and wisdom in human life, especially in the pursuit of happiness for those who enter into it. Building a good and happy family is the primary goal in every marriage. However, in practice, Islamic law often faces challenges in achieving this goal. One such challenge is unregistered (sirri) marriage, which, from the outset, allows for the potential emergence of harm within the household. Sirri marriage comes in various forms, such as not being registered by the state, not being publicly disclosed, or lacking witnesses in the process. The state does not accommodate the legal consequences arising from sirri marriages for the children and wives involved. Therefore, protection for children and wives affected by sirri marriage must be ensured to guarantee their justice and well-being.